Amazon Web Services (AWS) Video Website Hosting - Lee, Kuan Kin (2021)
These Days video websites are very popular, as many internet users enjoy their time they have spent over there. But many of the video websites still have some flaws. The first notably flaw is confused and unorganized user interface, a lot of websites lose their users due to this factor. Secondly, there are some video websites does not provide a good filter functions, it will cause users dissatisfaction. Thirdly, many of the video websites has no download functions embedded inside the website for them to download a video, the users usually have to go find a third-party tool online to do it. Cloud computing service is very popular as well, a lot of website hosting service has now turn to cloud web hosting to use its benefit to attract users to use their services. Amazon web service is a division of Amazon to provide cloud computing services to people and company. One of the service they provide is static website hosting. In this project, it will discuss how to develop a video website that will tackle the problems stated above to improve the video website. In order to tackle the problems stated above, this project will develop a video website that has user friendly interface, better filter function and download function. Beside that, the video website will be hosted on Amazon web service(AWS). This is due to AWS is very useful when it come to hosting static websites, it is also cheap when compare to other website hosting available in the internet.